2023
DOI: 10.1038/s41598-023-32894-w
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning of faciliatory paired-pulse TMS

Abstract: In this proof-of-concept study, we questioned whether the influence of TMS on cortical excitability can be applied to classical conditioning. More specifically, we investigated whether the faciliatory influence of paired-pulse TMS on the excitability of the human motor cortex can be transferred to a simultaneously presented auditory stimulus through conditioning. During the conditioning phase, 75 healthy young participants received 170 faciliatory paired TMS pulses (1st pulse at 95% resting motor threshold, 2n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“… 34 Depending on the intensity of conditioning stimulus (CS) and the test stimulus (TS) and ISI used, paired-pulse TMS is used to explore inhibitory or excitatory intracortical networks. 35 The short ISI (1–5 ms) with subthreshold CS and suprathreshold TS reaching 1.5 mV motor evoked potential (MEP) will produce short intracortical inhibition. 36 Reis et al 37 observed that increasing MEP amplitude with the ISI of 10–15 ms will produce a phenomenon known as intracortical facilitation.…”
Section: Methodsmentioning
confidence: 99%
“… 34 Depending on the intensity of conditioning stimulus (CS) and the test stimulus (TS) and ISI used, paired-pulse TMS is used to explore inhibitory or excitatory intracortical networks. 35 The short ISI (1–5 ms) with subthreshold CS and suprathreshold TS reaching 1.5 mV motor evoked potential (MEP) will produce short intracortical inhibition. 36 Reis et al 37 observed that increasing MEP amplitude with the ISI of 10–15 ms will produce a phenomenon known as intracortical facilitation.…”
Section: Methodsmentioning
confidence: 99%